Identification of Ralstonia solanacearum resistant solanum plants as potential rootstock to manage bacterial wilt disease in tomato production - Joseph Adomako; Michael Kwabena Osei; Ruth N. A. Prempeh; Isaac Osei-Bonsu; Joseph Gyau; Patrick Ofori; Isaac Newton Boakye-Mensah; Myeong-Cheoul Cho (Technology in Horticulture)
Using morphological and molecular markers, this study screened tomato (Solanum lycopersicum) and garden egg (Solanum melongena) accessions for resistance to bacterial wilt disease. The solanum plants were inoculated with Ralstonia solanacearum and evaluated for disease incidence and severity in a field trial set up in a Randomised Complete Block Design with four replications. Molecular markers conferring resistance to R. solanacearum Phylotype I and II were used to identify durable and partial resistance. Results showed significant variation in disease incidence and severity among accessions, with tomato accessions exhibiting higher susceptibility. Accession CRI-01 had the highest disease incidence (54.0%), while accession GD had the lowest (13.0%). Accession CRI-04 showed moderate resistance with a disease severity index of 0.37, while accession GC had the highest disease severity index (0.90). Accession L_020 demonstrated moderate resistance in the field (43.0% disease incidence) and possessed durable resistant genes, making it a promising rootstock for managing bacterial wilt disease in tomato production. This research contributes to the development of integrated pest management strategies for sustainable tomato production.